On Theoretical, Practical and Global Rationality in Robert Audi’s Philosophy - Dąbrowski, Andrzej (Analiza, racjonalność, filozofia religii: Księga jubileuszowa dedykowana Profesorowi Ryszardowi Kleszczowi. Nr 6 (2020), 2020)
The main purpose of this paper is to present Robert Audi’s philosophy of rationality. The task is performed against the background of analyzes and foundamental findings in Ryszard Kleszcz’s conception of rationality. The Polish philosopher critically reviews the most significant concepts of rationality used in various contexts, especially in philosophical discourse, and proposes his own solution: a two-tier model of rationality. At one level of this model, there are general principles („meta-principles”). At the other, more specific types of rationality. Hence, he differs from Audi. The American philosopher starts from elementary sensual experience and studies the dynamics of the cognitive process. He juxtaposes two basic rationalities: theoretical and practical. Audi discusses basic sources of knowledge and justifications, including inferential justification, and analyzes basic sources of practical rationality: desires, motives, intentions, means, and goals. He exposes similarities and differences between theoretical and practical rationality, and tests the extents to which these similarities can be integrated and provide an adequate explanation of global rationality.